Gingival cyst of the adult - Mota, Maria Emília; Oliveira, Dandara Menezes de Araujo; Medeiros, Yuri de Lima; Moreira, Maria Stella; Lopes, Rodrigo Nascimento; Alves, Fábio Abreu; Louredo, Brendo Vinícius Rodrigues; Vargas, Pablo Agustin; Prado, José Divaldo (Autopsy and Case Reports, 2023)
The gingival cyst of the adult (GCA) is a rare odontogenic cyst, consisting of 0.3% of all odontogenic cysts. This case report, based on CARE guidelines for case reports, aims to present a case of a 52-year-old female patient with a symptomatic translucent nodule in the upper left anterior gingiva, measuring approximately 6mm. Excisional biopsy was performed, and the histological examination revealed multiple cystic cavities lined by the squamous epithelium of varying thickness with focal areas of nodular thickenings. The presence of clusters of cells with clear cytoplasm within epithelial thickenings was observed. PAS staining was negative in clear cells. The diagnosis of the GCA was established. Despite its rarity, GCA should be considered in the differential diagnosis of gingival lesions. Conservative surgical treatment proved to be effective, with no signs of recurrence.